2012
DOI: 10.1371/journal.pone.0046791
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Fractional Anisotropy and Volumetric Abnormalities in Temporal Lobe Epilepsy: Cross-Sectional Evidence for Progressive Neurologic Injury

Abstract: BackgroundIn patients with temporal lobe epilepsy and associated hippocampal sclerosis (TLEhs) there are brain abnormalities extending beyond the presumed epileptogenic zone as revealed separately in conventional magnetic resonance imaging (MRI) and MR diffusion tensor imaging (DTI) studies. However, little is known about the relation between macroscopic atrophy (revealed by volumetric MRI) and microstructural degeneration (inferred by DTI).Methodology/Principal FindingsFor 62 patients with unilateral TLEhs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
91
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(111 citation statements)
references
References 81 publications
14
91
5
1
Order By: Relevance
“…Asymmetry in DTI findings was also found in other recent studies (Shon et al, 2010, Kemmotsu et al, 2011, Keller et al, 2012, with both MTS and non-MTS patients with left seizure onset having more significant and more widespread abnormalities, including atrophy, than right-onset patients.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Asymmetry in DTI findings was also found in other recent studies (Shon et al, 2010, Kemmotsu et al, 2011, Keller et al, 2012, with both MTS and non-MTS patients with left seizure onset having more significant and more widespread abnormalities, including atrophy, than right-onset patients.…”
Section: Discussionsupporting
confidence: 80%
“…These differences between LTLE and RTLE have been speculated to be due to greater vulnerability of the left hemisphere to early injury and the progressive effects of seizures (Kemmotsu et al, 2011), or a combination of architectural, connectivity, physiological and developmental differences between the hemispheres (Keller et al, 2012), however, further studies are required to investigate the cause of this asymmetry.…”
Section: Discussionmentioning
confidence: 99%
“…In 18 of the latter (47.4%), 14,16,[20][21][22]24,30,[33][34][35][36][37][38]40,42,[50][51][52] no statistical approaches were implemented to correct for the effects of age. Although the remaining studies addressed aging, no consistent method was chosen: 3 reported no significant effects of age on morphometric measures in controls, 15,32,48 3 found no effect of age or no effect of age at epilepsy onset in patients, 19,29,53 2 corrected for age at onset, 18,28 5 corrected for age in patients, 17,26,47,49,54 4 utilized MRI measures adjusted for age 13,31,39,46 (based on regression models derived from controls), 1 calculated epilepsy duration/age ratios, 23 2 statistically compared chronological age effects between patients and controls. 41,45 Among the longitudinal studies, 3 were singlecohort studies of patients without controls (interscan interval ranging from 2.3 to 3.4 years 27,41,44 ).…”
Section: Resultsmentioning
confidence: 99%
“…This is a new finding and suggests that left TLE may be associated with a bihemispheric hippocampal subfield alterations in these particular regions compared with right TLE, who showed evidence of reduced volumes in the contralateral hippocampal tail relative to patients with left TLE. There is an inconsistent literature on the effects of TLE laterality on the distribution of brain damage, with some indicating increasingly bilateral changes in left TLE,36, 37 in right TLE35, 38 and some studies suggesting equivalence 39. Just one of these studies39 has entered the hippocampal asymmetry (right>left) found in healthy controls14 as a confounding factor during statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of longitudinal data, cross‐sectional studies have correlated brain compartment volume with duration of epilepsy as a surrogate marker of progressive damage due to seizure chronicity. There is inconsistency in the literature with respect to relationships between hippocampal and extrahippocampal volume loss and duration of TLE 7, 10, 11, 36. Given that duration of epilepsy and chronological age are related, it is important to correct clinical correlations for patient age to determine whether brain atrophy is driven by epilepsy‐related factors or normal age‐related maturation.…”
Section: Discussionmentioning
confidence: 99%